Effects of Transcranial Direct Current Stimulation Combined With Physical Training on the Excitability of the Motor Cortex, Physical Performance, and Motor Learning: A Systematic Review - Wang, Baofeng; Xiao, Songlin; Yu, Changxiao; Zhou, Junhong; Fu, Weijie (Frontiers in Neuroscience, 2021)
Purpose: This systematic review aims to examine the efficacy of transcranial direct current stimulation (tDCS) combined with physical training on the excitability of the motor cortex, physical performance, and motor learning. Methods: A systematic search was performed on PubMed, Web of Science, and EBSCO databases for relevant research published from inception to August 2020. Eligible studies included those that used a randomized controlled design and reported the effects of tDCS combined with physical training to improve motor-evoked potential (MEP), dynamic posture stability index (DPSI), reaction time, and error rate on participants without nervous system diseases. The risk of bias was assessed by the Cochrane risk of bias assessment tool. Results: Twenty-four of an initial yield of 768 studies met the eligibility criteria. The risk of bias was considered low. Results showed that anodal tDCS combined with physical training can significantly increase MEP amplitude, decrease DPSI, increase muscle strength, and decrease reaction time and error rate in motor learning tasks. Moreover, the gain effect is significantly greater than sham tDCS combined with physical training. Conclusion: tDCS combined with physical training can effectively improve the excitability of the motor cortex, physical performance, and motor learning. The reported results encourage further research to understand further the synergistic effects of tDCS combined with physical training.